Product-Focused Software Process Improvement 14th International Conference, PROFES 2013, Paphos, Cyprus, June 12-14, 2013, Proceedings - Heidrich, Jens; Oivo, Markku; Jedlitschka, Andreas; Baldassarre, Maria Teresa (Programming and Software Engineering, 2013)
This book constitutes the refereed proceedings of the 14th International Conference on Product-Focused Software Process Improvement, PROFES 2013, held in Paphos, Cyprus, in June 2013. The 22 revised full papers presented together with 10 short papers and 2 tutorial papers were carefully reviewed and selected from 41 submissions. The papers are organized in topical sections on empirical software engineering, software process improvement, managing software processes, software measurement, decision support in software engineering, safety-critical software engineering, and software maintenance.